(untitled) (Research, Society and Development, 2024)
Objectives: to evaluate, in a retrospective and observational manner, the success rates in endodontic retreatment of molars over 11 years in a brazilian population. Methods: 280 cases were analysed based on clinical data from dental records and digital x-rays, obtained at the EndoMais Private Dental Clinic (Uberlândia/Minas Gerais/Brazil), from may/2012 to may/2023. All portraits investigated were carried out using an operative scope and by a single endodontist. The Periapical Index (PAI) was used to complement the radiographic analysis, by quantifying the presence of periapical changes. After applying the inclusion and exclusion criteria, a total of 56 cases were obtained. Results: the success rate in molars endodontic retreatment was 67,85%. Among the 32,15% of failure in this procedure, signs and symptoms were found in 12.5% and 7.14%, respectively, 28.57% had a periapical lesion, 32.14% still had unsatisfactory filling and 3.57% unsatisfactory sealing. Conclusion: the intraradicular and extraradicular infection were the principal cause of endodontic retreatment’s cases. Root canal filling’s quality and post treatment restauration should be considered as important topics to a major success’ rate.